Social Assistance System in Poverty Reduction in Indonesia and the Philippines - Liya Yulia; Binahayati Rusyidi; Sri Sulastri (Budapest International Research and Critics University, 2022)
Poverty is increasing in the midst of the Covid-19 pandemic situation. Southeast Asian countries seek to reduce poverty through various social protection programs. Social protection in Indonesia and the Philippines applies a social assistance approach as a basic aspect of service delivery. This article aims to analyze the social assistance system in Indonesia and the Philippines in tackling poverty. The research method uses a literature study approach obtained from various reliable sources such as reputable journals, books, program reports, electronic media. The results showed that both programs were implemented by means of Conditional Cash Transfer (CCT). The target of the program in Indonesia is more inclusive because the elderly and disabled can be the beneficiaries. Then in the termination of membership, In Indonesia, there is an independent graduation mechanism where the assessment benchmark is based on the economic independence of the beneficiary. Meanwhile in the Philippines, the mechanism for termination of participation is only carried out if the beneficiary does not meet the requirements of the age of the child only.